The PERBANDINGAN EFEKTIVITAS YOGA PRENATAL DAN SENAM HAMIL TERHADAP PENURUNAN NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III : STUDI KUASI EKSPERIMENTAL - Sukati Sarmin; Fifi Ratna Aminati; Arista Kusuma Wardani (LPPM Universitas Abdurrab, 2026)
Low back pain is often experienced by pregnant women, especially during the third trimester, due to changes in posture, weight gain, and stretching of muscles and ligaments during pregnancy. The percentage of this complaint increases from 16% in early pregnancy to 67% at 24 weeks and peaks at 93% at 36 weeks. Various non-medical approaches have been implemented to address this complaint, including prenatal yoga and prenatal exercise. This study aimed to compare the effectiveness of prenatal yoga and prenatal exercise in reducing low back pain in pregnant women in the third trimester. This study used a quantitative method with a two-group quasi-experimental pretest-posttest design. The study sample consisted of 40 pregnant women in their third trimester selected using purposive sampling and divided into two groups: the prenatal yoga group and the prenatal exercise group, each with 20 respondents. The intervention was provided twice a week for 60 minutes each session under the guidance of an experienced instructor and supported by leaflets and videos. The level of low back pain was measured using the Numeric Rating Scale (NRS). Data analysis was performed using a dependent t-test followed by an independent t-test. The results showed that both prenatal yoga and prenatal exercise were equally effective in reducing low back pain in pregnant women in the third trimester (p=0.001; p<0.05). However, there was a significant difference in effectiveness between the two interventions (p=0.000; p<0.05), with prenatal yoga providing a greater reduction in pain. These findings suggest that prenatal yoga is more effective than prenatal exercise in reducing low back pain in pregnant women in the third trimester because it combines stretching, relaxation, breathing control, and muscle strengthening exercises that support postural stability during pregnancy